Unsuccessful removal of a totally implantable venous access port caused by thrombosis in the left brachiocephalic vein: A case report. Issue 13 (March 2019) - Zhang, Xi; Geng, Cuizhi
Abstract: Rationale: Thrombosis is a common complication associated with implantable venous access ports (IVAPs) and often results in loss of catheter function but is rarely associated with difficulty in IVAP removal. Patient concerns: A 53-year-old woman presented to the hospital due to difficulty in IVAP removal. The patient had been diagnosed with breast cancer and received modified radical mastectomy. After that, she underwent IVAP implantation. Four and half years later, the IVAP catheter had become stuck while the catheter remained unobstructed. The patient had no special chief complaints. Diagnosis: Postoperative breast cancer; difficulty in removal of IVAP (caused by thrombus in the left brachiocephalic vein). Interventions: We injected urokinase 5 ml 1000U/L into the catheter once a day for three days but failed to remove the IVAP. Vasography showed a thrombus in the left brachiocephalic vein. Removal of the thrombus would have been very dangerous, so we decided to leave both thrombus and catheter in the body and used heparin and warfarin as anticoagulants. Outcomes: The general situation of the patient, followed-up for 20 months, was good and there was no psychological impact or other special chief complaints. Lessons: It is best to remove the IVAP in a timely manner once all treatments are finished.